Israel : Staff Report for the 2001 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2001)
The Israeli economy has seen both rapid growth and price stability, and subsequently a very sharp deceleration. The design and execution of fiscal policy have improved markedly in recent years, but further progress is needed. It is also important to make further, steady progress with the structural and institutional reform agenda to create a more efficient and flexible economy and to enhance future growth prospects. Data provision is generally adequate for surveillance purposes, though the quality of some statistics could be enhanced.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet